The association between short-term apparent temperature exposure and human coagulation: A time-series study from Beijing, 2014–2023 - Yi Zhang; Tiancheng Wang; Jiaqi Shi; Ying Ma; Nairui Yu; Xinyan Zhou; Pai Zheng; Zhangjian Chen; Guang Jia (Environment International)
A growing body of evidence suggests that non-optimal ambient temperatures are associated with increased incidence rate and mortality of thromboembolic diseases. We aim to investigate the association between apparent temperature (AT) and coagulation, which is a central pathological link in the formation of thrombi. In this study, we conducted a time series analysis using data from 18,894 participants collected from a health check-up center in Beijing between 2014 and 2023, and validated our findings using 20,549 participants from an andrology outpatient clinic. The daily mean AT was calculated using data on ambient temperature, relative humidity, and wind speed from Beijing. Participants were matched to the lagged moving average of AT (0–7 days) based on their specific health examination dates. The study employed generalized additive models to analyzed the linear and nonlinear associations between AT and coagulation indices. The results indicated that heat resulted in shortened prothrombin time and activated partial thromboplastin time, whereas cold resulted in shortened thrombin time. Fibrinogen showed an increase at both high and low temperatures. Logistic regression analysis revealed that the risk of hypercoagulable state increased in both high and low temperature environments compared to moderate temperatures, with a significant increase observed under extreme heat conditions. Subgroup analyses by sex and age, sensitivity analyses, and the external validation indicated that the association between AT and coagulation was robust. The findings support that both cold and heat can augment blood coagulability through distinct stages of the coagulation cascade, thereby leading to an elevated risk of thromboembolic diseases.